Autotransporter Adhesins in Escherichia coli Pathogenesis. Issue 23 (12th October 2017) - Vo, Julieanne L.; Martínez Ortiz, Gabriela Constanza; Subedi, Pramod; Keerthikumar, Shivakumar; Mathivanan, Suresh; Paxman, Jason J.; Heras, Begoña
Abstract: Most bacteria produce adhesion molecules to facilitate the interaction with host cells and establish successful infections. An important group of bacterial adhesins belong to the autotransporter (AT) superfamily, the largest group of secreted and outer membrane proteins in Gram‐negative bacteria. AT adhesins possess diverse functions that facilitate bacterial colonisation, survival and persistence, and as such are often associated with increased bacterial fitness and pathogenic potential. In this review, we will describe AIDA‐I type AT adhesins, which comprise the biggest and most diverse group in the AT family. We will focus on Escherichia coli proteins and define general aspects of their biogenesis, distribution, structural properties and key roles in infection.